2016
DOI: 10.1007/s10508-016-0746-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Sexual Offending in Men Working With Children: A Community-Based Survey

Abstract: Identifying risk factors for sexual abuse in men who work with children and who have already abused a child could lead to more appropriate screening and prevention strategies and is thus of major scientific and societal relevance. A total of 8,649 German men from the community were assessed in an extensive anonymous and confidential online survey. Of those, 37 (0.4%) could be classified as child sexual abusers working with children, 90 (1.0%) as child sexual abusers not working with children, and 816 (9.4%) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…The survey (constructs described in order of appearance in the survey) consisted of a multimethod approach tapping into sexual fantasies and behaviors involving prepubescent children and adults. For the sake of method transparency a full description of all measures included in the survey is listed here, although not all measuresparticularly the indirect latency-based and indirect questioning measures-fall within the scope of this report and therefore are reported elsewhere (e.g., Turner, Hoyer, Schmidt, Klein, & Briken, 2015).…”
Section: Measures and Survey Proceduresmentioning
confidence: 99%
“…The survey (constructs described in order of appearance in the survey) consisted of a multimethod approach tapping into sexual fantasies and behaviors involving prepubescent children and adults. For the sake of method transparency a full description of all measures included in the survey is listed here, although not all measuresparticularly the indirect latency-based and indirect questioning measures-fall within the scope of this report and therefore are reported elsewhere (e.g., Turner, Hoyer, Schmidt, Klein, & Briken, 2015).…”
Section: Measures and Survey Proceduresmentioning
confidence: 99%
“…Another study found that men who had sexually abused children in the context of work had higher rates of pedophilic diagnoses but lower rates of antisociality compared with men who had sexually abused children in nonwork-related contexts (Turner, Rettenberger, Lohmann, Eher, & Briken, 2014). In a large epidemiological study of men unselected for attraction to children or adults, there was a small, statistically significant association between working with children and reporting sexual contact with them (Turner, Hoyer, Schmidt, Klein, & Briken, 2016).…”
Section: The Present Studymentioning
confidence: 99%
“…In den vergangenen ca. 20 Jahren wurden allerdings männliche Betroffene sichtbarer, im deutschsprachigen Raum insbesondere im Zusammenhang mit der Missbrauchsdebatte im Umfeld von Schulen und Kirche [3]. Daraus folgte ein anhaltender veränderter Diskurs.…”
Section: Caveunclassified